Proceedings of the 29th ACM/IEEE International Conference on Automated Software Engineering 2014
DOI: 10.1145/2642937.2642949
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-based auto-completion of UML modeling activities

Abstract: Auto-completion of textual inputs when using IDEs benefits software development experts and novices. Researchers demonstrated that auto-completion is beneficial for graphical modeling tasks as well. However, supporting software development by auto-completing UML modeling activities remains largely unexplored by research and unsupported by modeling tools. By matching editing operations to activity patterns, partly performed modeling activities can be recognized and automatically completed. This paper proposes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Focusing on the field of software and system modeling, existing assistants together support all key aspects of the system life-cycle of increasingly complex systems. Large efforts have gone into supporting common modeling languages like UML, e.g., to support a particular modeling process [37], and to help build diagrams from natural language [21] or through recommendations from similarities [16] or established patterns [25]. However, it is very time-consuming to build similar IMAs for the diverse set of other domain-specific abstractions that are tailored to heterogeneous stakeholders.…”
Section: Assessment Of Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing on the field of software and system modeling, existing assistants together support all key aspects of the system life-cycle of increasingly complex systems. Large efforts have gone into supporting common modeling languages like UML, e.g., to support a particular modeling process [37], and to help build diagrams from natural language [21] or through recommendations from similarities [16] or established patterns [25]. However, it is very time-consuming to build similar IMAs for the diverse set of other domain-specific abstractions that are tailored to heterogeneous stakeholders.…”
Section: Assessment Of Related Workmentioning
confidence: 99%
“…All existing IMAs focus only on syntactic model quality (Level 1 of Quality of IMA Regarding Model), i.e., they do not consider semantic or pragmatic quality, except for one case of semantic quality ( [8]). The majority of existing IMAs remains at low levels of autonomy (Level 0 or 1), but there are four cases with higher autonomy ( [8,12,16,25]). None of the existing IMAs report on relevance (Level 0) or confidence (Level 0), or provide information about trust (Level 0), except for one case with high relevance ( [12]).…”
Section: Assessment Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been demonstrated that assistance functions are beneficial in these domains [5] [6], assistance functions are not considered in commercial BPM tools. However, since recommender systems "generate meaningful recommendations to a collection of users" [7], development activities towards such systems should be given a priority in order to offer assistance functions in process modeling tools too.…”
Section: Motivation and Relevancementioning
confidence: 99%
“…In previous work, we used complex patterns of editing events to update traceability information automatically upon recognizing users' modeling activities [7] and successfully brought a visual language approach to traceability analysis [8][9][10]. In a succeeding project, we studied how software modeling activities can be recommended while a developer is editing UML models [11] and how such recommended activities can then be auto-completed [12][13][14]. Both proposed approaches build upon activity definitions captured as event-processing rules.…”
Section: Introductionmentioning
confidence: 99%